THE EFFECT OF JOB TRAINING, FINANCIAL COMPENSATION, AND WORK LOYALTY ON EMPLOYEE PERFORMANCE AT PT. PLN KRUENG GEUKUEH - Muhammad Abdul Kahfi; Nurmala; A Hadi Arifin; Sullaida (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This research aims to examine the influence of Job Training, Financial Compensation and Work Loyalty on Employee Performance at PT. PLN Krueng Geukueh. The data used in this research is primary data obtained by distributing questionnaires to 56 respondents. The data analysis technique used is multiple linear regression analysis using the Statistical Program for Product and Service Solution (SPSS) version 25 software. The results of the research show that there is a positive and significant influence between job training on employee performance, financial compensation has a positive but not significant influence on employee performance and the influence of work loyalty has a positive and significant influence on employee performance.